KONTESTASI PEMAKNAAN RITUAL TABUT (PERSPEKTIF IDEOLOGI DAN KEKUASAAN) - Femalia Valentine; Taufik R Talalu (Farabi, 2022)
There is a contention between the government and the Tabut enthusiast. Through the political and economic power, the government made Tabut as a cultural commodity while Tabut enthusiast continue to maintain the existence of the sacred of the Tabut ritual with the symbolic power they have. The contention should not be a conflict trigger, but understood as a treasure and diversity of thoughts in understanding culture of plural society in Bengkulu. This paper describes the factors that cause contention in the perspective of Islamic communication, ideological theory and power, reasons for diversity in the concept of pluralism can lead to contention of meaning and reasons for discourse and lived culture can be a diversity of thoughts. This research uses ideology and power theory approach, which explains about ideology in Marx’s view, pluralism, discourse, and lived culture. This relation involves ideologies and strengths of each group. It is also creating pluralism that positions the government of Bengkulu as the holder of political and economic power which in the end of gave rise to Tabut Pembangunan as a tourism commodity that aim to improve the community’s economy.